Unpacking Structural Poverty through a Sustainable Economic Lens: A Qualitative Literature Review - Muhamad Fardan; Hariyono (International Conference on Islamic Economic (ICIE), 2025)
Structural poverty represents a persistent form of deprivation that arises from systemic social and economic inequalities, yet it has not been sufficiently addressed within the framework of sustainable development. This gap is critical because sustainable development goals inherently emphasize inclusivity, justice, and long-term equity. The purpose of this study is to analyze how structural poverty is conceptualized and interpreted in relation to sustainable economics, as well as to explore its implications for achieving sustainability-oriented policies and practices. This research employs a qualitative literature review, systematically analyzing scholarly publications from the last ten years. Thematic analysis was applied to identify dominant themes, theoretical orientations, and empirical findings concerning the nexus of poverty and sustainability. The results show that structural socio-economic inequalities remain a major barrier to fulfilling sustainable development goals, particularly those related to social and economic justice. Moreover, the study provides a conceptual mapping that highlights how interdisciplinary approaches—from economics, sociology, and environmental studies—offer valuable insights into addressing the systemic roots of poverty. The contribution of this study lies in deepening theoretical understanding while simultaneously offering practical relevance. It underscores the urgency of integrating structural poverty into sustainability discourse and suggests that future policy must address systemic inequalities to promote more equitable and sustainable development.